Safety and efficacy of programmed cell death-1 inhibitors in relapsed immune-privileged site lymphoma: A systematic review and meta-analysis - Ekdanai Uawithya; Kamolchanok Kulchutisin; Jiraporn Jitprapaikulsan; Nattawut Leelakanok; Weerapat Owattanapanich (PLoS ONE, 2025)
Background Large B-cell lymphoma of immune-privileged sites (LBCL-IP) is a rare subtype characterized by immune evasion properties. Primary central nervous system lymphoma (PCNSL) and primary testicular lymphoma (PTL) are examples of LBCL-IP associated with programmed cell death protein 1 (PD-1). Few studies have investigated the use of PD-1 inhibitors in patients with relapsed PCNSL and PTL. Objective To conduct a systematic review evaluating the efficacy and safety of PD-1 inhibitors in patients with relapsed PCNSL and PTL. Methods We searched the PubMed, Embase, and Scopus databases for relevant studies. The inclusion criteria focused on adult patients diagnosed with relapsed PCNSL or PTL who were treated with PD-1 inhibitors. We excluded case reports or series with fewer than five participants, review articles, and animal studies. A random-effects model with the DerSimonian‒Laird method analyzed the pooled complete response rate (CRR), partial response rate (PRR), overall response rate (ORR), and progression-free survival (PFS) rate. Results Seven studies comprising 127 patients (124 with relapsed PCNSL and 3 with PTL) were included. All patients were treated with either nivolumab or pembrolizumab. The pooled CRR was 42.8% (95% CI, 25.7%‒60.0%; I2 = 75.25%; p < 0.001), indicating high heterogeneity. The pooled PRR was 17.1% (95% CI, 9.5%‒24.7%; I2 = 18.71%; p = 0.287), with nonsignificant heterogeneity. The pooled ORR was 67.1% (95% CI, 44.9%‒89.4%; I2 = 88.64%; p < 0.001), indicating high heterogeneity. The 6-month PFS rate was 34.8% (95% CI, 18.1%‒51.5%; I2 = 27%; p = 0.242), with low heterogeneity. Thirty-eight adverse events were reported. The most common were skin reactions (14 events; 36.8%), fatigue (11 events; 28.9%), and nausea (6 events; 15.8%). Conclusions Our study demonstrates that PD-1 inhibitors show promising efficacy in relapsed PCNSL and PTL, with significant responses observed. The adverse effects were mild, with the most common being skin reactions. Therefore, PD1 inhibitors have the potential to drive advancements in treatment strategies for relapsed PCNSL and PTL.